Environmental awareness in China: Facilitating the greening of the economy - Guo, X.; Marinova, Dora (The Modelling and Simulation Society of Australia and New Zealand Inc., 2011)
China’s miraculous economic growth (at an average rate of 10% per annum for over three decades) has come under a strong criticism because of the country’s increasing environmental deterioration. In 2007, China officially became the top global greenhouse gas (GHG) emitter and its natural environment has suffered severe deterioration while the country’s governments had been focusing predominantly on economic growth without paying significant attention to the ecology. Recently however with the country’s 12th Five-Year Plan the government adjusted China’s national development strategy towards addressing climate change and achieving a low-carbon economy which considers the global impact from the country’s economic development. The foundation for developing a low-carbon economy in China lays in enhancing its environmental education system and overall environmental awareness. This paper analyses the increase in environmental awareness in China based on the conceptual sustainability model. It uses data to describe community, government and media engagement with environmental issues and analyses the trends in activities, such as public petitions, government reports and media news/articles. It shows that the government has gradually increased the attention paid to environmental issues, including adopting a wide range of new policy documents and encouraging environmental education programs. Protecting the environment has also become a highly important topic of media coverage in all Communist Party controlled provincial newspapers with overall more than 8,000 counts of environmentally related news/articles in 2009 (or around 22 per day) and the two main Chinese newspapers, Beijing Daily and Liberation Daily providing highly comprehensive environmental reports.Public participation around ecological issues has also been on the rise with high numbers of environmental petitions and proposals reaching the National People’s Congress (NPC) and the Committee of the Chinese People's Political Consultative Conference (CPPCC). The paper concludes that despite the fact that environmental awareness and environmental concerns have become more and more visible within the Chinese society, there is still a strong need to improve environmental education and government policies in order to achieve a harmonious transformation of China’s economy. For example, a lot more scientific, technological and managerial personnel for environmental protection work should be provided by the Chinese higher education system to accommodate the need for developing a low-carbon economy. Also, in the search of solutions the Chinese governmental and non-government organizations can be involved in developing a better relationship between people and their natural environment by absorbing nourishment from the Chinese cultural genes, such as the ancient wisdom of Confucianism. Although China has set up high goals to achieve and has already established a complete environmental management system, this country is still in need of a better environmental awareness and effective implementation of environmental management, laws and regulations.